Exploring Ambiverted Tutor Strategies: A Narrative Inquiry into Enhancing English Speaking Skills for Young Learners - Suci Fitriyani; Nunun Indrasari; Istiqomah Nur Rahmawati (Lingual: Journal of Language and Culture, 2025)
This qualitative research focuses on the strategies applied by ambivert personality tutor to enhance young learners' English-speaking skills. The research is motivated by the complex challenges in teaching speaking, such as language anxiety, heterogeneity of abilities, and low confidence of learners in Indonesia. The participant, an ambivert tutor, was selected purposively to represent reflective yet adaptable teaching characteristics. This research used the narrative inquiry method to explore the experiences of an ambivert tutor in depth. Data were collected through semi-structured interviews, narrative frames, and lesson plans document analysis, then thematically analyzed. The research findings reveal that the participant's philosophy, which focuses on building confidence and joy, is consistently implemented through various communicative strategies. Participant also responsively address the key challenges of ability heterogeneity and classroom energy management through differentiated instruction strategies and positive non-verbal classroom management.